PENGARUH LATIHAN STRENGTH HAND WALKING TERHADAP KEKUATAN OTOT LENGAN TIM BOLAVOLI MINAS - Dicky Martha; Zainur Zainur; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this study was to determine the effect of exercise strength hand walking on the muscle strength of the Minas Bolavoli Team. The population and samples in this study were the 10 Minas Bolavoli Team. The instrument used to collect data namely the pree test and post test in this study used arm muscle strength tests with the Knee Push Up Test. The data analysis technique used is the t test. Based on the results of the research that has been done, it shows that the average value at the time of the post test is greater than the average value when doing the pree test which is equal to 20.80 > 15.70, this means that after being given strength hand walking exercises 16 times , the muscle strength of the Minas Bolavoli Team is better than before. Based on the results of the analysis of pree test and post test data there was an increase of an average of 32.48% with a t test that t = 11,135> from t table = 1,833. So with this it can be concluded that there is the effect of strength training hand walking on the muscular strength of the Minas Bolavoli Team.Keywords: Strength Hand Walking Exercises, Arm Muscle Strength